BIMBINGAN BELAJAR BAHASA INGGRIS TINGKATKAN KEMAMPUAN KOMUNIKASI DAN LITERASI ANAK DESA KUDADEPA - Hana Supratna; Hardi Humaedi; Aghni Raihan; Jafira Nur Asria; dina indriani atikah (LPPI UMN AL WASHLIYAH, 2025)
This community service program aims to improve the English language skills of children in Kudadepa Village, who face challenges in accessing English language learning. The lack of educational facilities and infrastructure, as well as the limited number of teachers, are some of the barriers. Through a fun and interactive learning approach, this program strives to enhance speaking, listening, reading, and writing skills in English among the children of Kudadepa Village over the course of 5 weeks. The methods used include language games, singing, and demonstrations. Evaluation results show improvements in speaking and reading skills. Additionally, the program successfully boosted students' confidence and motivation to learn. The success of this program highlights the importance of broader access to quality English language education for children in rural areas.